CUSTODIAL DEATHS: AN UNADDRESSED ISSUE - Chahal, Preetinder Singh; Aggarwal, Akashdeep; Singh, Satinder Pal; Kakkar, Gurvinder Singh; Kumar, Deepak (Journal of Forensic Medicine and Toxicology, 2021)
Death in custody is usually associated with apprehension and community concern and raises the suspicion of violation of human rights. Studies conducted in few countries have shown that people in custody have increased rate of morbidity and mortality than those not in custody. Many of these deaths are premature deaths and can be prevented with proper care and treatment. The present post-mortem examination based retrospective study was undertaken regarding deaths in custody and provide mortality patterns. A total 75 autopsies were performed in custodial deaths during the 4year period out of which 72(96%) cases were of natural deaths. Among the natural causes of death, multiple organ failure was observed in a majority of the cases (32%). Among the unnatural causes of death, poisoning was observed more commonly than hanging. Male preponderance (94.6%) was observed and most of cases were in 21-40 age group (46.66%). Most of the victims were Sikhs (50.7%) followed by Hindus. Majority of deaths were observed in victims who were lodged in jails for less than 6 months (26.7%). As most of deaths in custody are due to natural causes, appropriate and timely care should be provided to prison inmates to be adopted to reduce morbidity and mortality and prevent allegation of lack of care of prisoners.
Keywords: Custody; Death; Autopsy; Human Rights; Natural Disease